ANALYSIS OF TOMATO FARMING INCOME IN KARO REGENCY, NORTH SUMATRA - Faisal Azhari Baldan Panjaitan; Nadila Savira; Aadil Hussain Mir (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to analyze the production costs, revenues, and income of tomato farming in Karo Regency, North Sumatra. This study used a survey method with a quantitative descriptive approach. The sample was determined using a saturated sampling method, with all 20 tomato farmers as respondents. The data used consisted of primary data obtained through interviews using questionnaires and secondary data from relevant agencies. Data analysis was conducted using cost, revenue, and farm income analysis. The results showed that the average total production cost of tomato farming was IDR 2,680,655 per planting season, consisting of fixed costs of IDR 733,605 and variable costs of IDR 1,947,050. The average income received by farmers was IDR 21,401,100, while the average revenue was IDR 18,720,445 per planting season. The R/C ratio of 8.01 indicates that tomato farming in Karo Regency is very feasible and profitable to develop. Thus, tomato farming in Karo Regency has good prospects for increasing farmer income. However, farmers still face challenges such as price fluctuations and high production costs, necessitating increased efficiency in the use of production factors and policy support from the local government to improve farmer welfare.